2002
DOI: 10.2298/gensr0201033b
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of stay green trait in maize

Abstract: Genetic variation for stay green character has been exploited in maize improvement mainly in the light of selecting high yielding rather then typical stay green genotypes. Stay green is an indicator of good plant health later in the season, reduced progressive senescence, tolerance to post-flowering drought and stalk lodging, what ensure superiority of stay green genotypes in comparison to non-stay green ones, especially in drought conditions. The objective of the study was to examine relationship of stay gree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…We therefore assume that a drying stem would possibly lead to faster grain drying and lower grain moisture at harvest time, which typically is not a factor in sweet sorghum production. In a previous study regarding relationships of stay green trait in maize, the grain moisture at harvest time was highly significantly correlated with stalk water content [ 38 ]. Thus the fine mapping of the dry stalk locus in present study could be applied in marker assisted selection program for more timely harvest in both biomass and grain sorghums and shed some light on other important crops like corn and rice etc.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore assume that a drying stem would possibly lead to faster grain drying and lower grain moisture at harvest time, which typically is not a factor in sweet sorghum production. In a previous study regarding relationships of stay green trait in maize, the grain moisture at harvest time was highly significantly correlated with stalk water content [ 38 ]. Thus the fine mapping of the dry stalk locus in present study could be applied in marker assisted selection program for more timely harvest in both biomass and grain sorghums and shed some light on other important crops like corn and rice etc.…”
Section: Discussionmentioning
confidence: 99%
“…Diff1 and Diff2 could indicate the stay-green phenotype. In other word, delayed leaf senescence (stay-green) indicates the performance of maize to maintain normal metabolic processes under abiotic stress [33][34][35][36][37][38]. A study suggested that a lower rate of chlorophyll loss was often used as an indicator for selecting potato plants with drought tolerance [33].…”
Section: Phenotypic Analysis and Smith Indice Estimation For 34 S 2 F...mentioning
confidence: 99%
“…Stay green is an indicator of good plant health especially in drought conditions, which leads to reduced senescence, adaptability to stalk lodging, and post-flowering dehydration. This trait ensures superiority of plants compared to non-stay-green ones [41]. When green plant tissue area contributes more than the average of total plant area, and the grain moisture is lower or equal to the population average, that plants are regarded as stay green [42].…”
Section: Stay Green (Sg)/non-senescencementioning
confidence: 99%